Darriwilian (Middle Ordovician) worms of southern Sweden. (1st October 2016) - Eriksson, Mats E.; Lindskog, Anders; Servais, Thomas; Hints, Olle; Tonarová, Petra
Abstract: The record of scolecodonts (polychaete jaws) from the Ordovician of Sweden is very poor. In this paper, we document a Darriwilian (Middle Ordovician) assemblage recovered from palynological samples from the "orthoceratite limestone" (Lanna and Holen limestones) of Mount Kinnekulle, Västergötland, southern Sweden. The collection of diminutive specimens forms an assemblage taxonomically composed mainly of simple placognath (mochtyellids, xanioprionids) and ctenognath (tetraprionids) taxa, whereas labidognaths (polychaetaspids) and taxa with other evolutionary grade-type apparatuses are very rare or absent. In addition, putative priapulid (penis worm) teeth were identified, possibly representing the first fossil representatives recorded in Sweden. The highest scolecodont abundance coincides with the lower to middle part of the "Täljsten" interval (lower Kunda Baltoscandian Stage). These strata are interpreted as having been formed during a marked regressional phase, suggesting that the palaeobathymetry and/or bottom substrate was optimal for polychaete colonization at that time. This new assemblage from Kinnekulle adds to the global scolecodont record in which data on Middle Ordovician and older specimens are still rudimentary but of importance for understanding early polychaete phylogeny.